Cystic fibrosis: a model for precision medicine. Issue 2 (4th March 2018) - McNally, Paul; Greene, Catherine M.
ABSTRACT: Introduction : Cystic Fibrosis is a recessive monogenetic disease caused by mutations in the gene encoding the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR), a chloride ion channel expressed by epithelial cells throughout the body. Although it is a multisystem disease, for most patients the pulmonary manifestations of CF account for the major incidences of morbidity and mortality. Areas covered : In this review, the authors discuss new and emerging therapies that target CFTR and describe ex vivo models that have been developed to evaluate the efficacy of precision medicines for people with CF. Expert commentary : Pharmacological and genetic medical technologies to overcome CF have been developed. These treatments are expensive but for people with CF, and especially those with rare CFTR mutations, strategies exist to test appropriate drug doses and combinations thereof ex vivo . The current challenges are to identify the correct CFTR therapy for each patient and make a clinical decision about when that therapy should begin. Notwithstanding the potential effectiveness of these medications, adjunct therapies may also be necessary to treat the infective and inflammatory manifestations of CF lung disease.